CNS active O-linked glycopeptides - Jones, Evan M.; Polt, Robin (Frontiers in Chemistry, 2015)
Naturally occurring glycopeptides and glycoproteins play important roles in biological processes. Glycosylation is one of the most common post-translational modifications in vivo. Glycopeptides are involved in cell signaling and sorting, providing cell surface markers for recognition. From the drug design and synthesis perspective, modification of a peptide through glycosylation results in increased bioavailability and bioactivity of glycopeptides in living systems with negligible toxicity of degradation products. Glycopeptide synthesis can be accomplished through incorporation of a glycosylated amino acid in solid phase peptide synthesis (SPPS) to form the desired peptide, or via incorporation of sugar-amino acid moieties. Additionally, research indicates that glycosylation increases penetration of the blood-brain barrier (BBB) by peptides, which may lead to novel therapeutics for neurological disorders. Recent applications of glycopeptides have focused on the in vivo central nervous system effects after peripheral administration of centrally active peptides modified with various carbohydrates.